Effect of Cueing on Learning Transfer Among Pre-professional Undergraduate Healthcare Students Engaged in a Case-based Analogical Reasoning Exercise - Timothy E. Speicher; Marijke T. Kehrhahm; Alexandra Bell; Douglas J. Casa (Adult Education Research Conference, 2011)
To examine the extent of transfer of cued versus non-cued pre- professional healthcare undergraduates engaged in a case-based analogical reasoning exercise. Independent t-test analysis and effect size was calculated to assess transfer between cued and non-cued participants (N = 192). Cued participants (n = 98, M = 2.30, SD = .89) demonstrated significantly more transfer (t (175.91) = 2.65; p = .009; CI95 = (.10, 0.68); d = .39) than non-cued participants (n = 94, M = 1.9, SD = 1.14). Learning transfer improves among pre- professional undergraduates when cued during a case-based analogical reasoning experience.
Keywords: cueing; transfer; analogical reasoning